Unfair Contract Laws in United Kingdom and Pakistan: A Critical Analysis - Shah Sawar Younas Khan; Adnan Asmat; Sana Ullah Saeed (Dialogue Social Science Review (DSSR), 2024)
The principle of fairness has been a fundamental aspects of contract law for a long time. The principle requires the parties to a contract to be clear and fair about the terms on which the parties are going to agree. The fairness principle put certain bars on persons/parties entering into a contract about the terms that may vitiate the agreeable terms in a long run. The contract may vary in terms of its significance and utility. The difference in contracts may exist like a business to a business contract or maybe a consumer contract. The concept of unfair contract laws means to explicitly bar any sort of fraudulent, deceptive or unfair practices in the market place, which may benefit one party while making the other miserable. The thesis is based on a comparative study of United Kingdom with Pakistan in terms of unfair contract laws. Based on qualitative research, the thesis comprised of an investigative approach while taking into account the laws regulating unfair contracts, their legislative foundations and judicial constructions of both jurisdictions. All around the world, the notion of unfair contract laws is prevalent while some are making reforms with the digitalization and globalization in the current era. Policy makers and legal professional are all of the view that thorough legislation is the need of time to address modern issues which arises due to unfair contract terms in contract. The researcher in the end have tried to propose certain recommendations to protect consumers and promote fair business practices in Pakistan.